EAGE Annual Conference &Amp; Exhibition Incorporating SPE Europec 2013
DOI: 10.2118/164881-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improved Petrophysical Analysis in Horizontal Wells: From Log Modeling Through Formation Evaluation to Reducing Model Uncertainty - A Case Study

Abstract: This paper presents the results of using a new workflow to correct and validate logging-while-drilling measurements (LWD) from horizontal wells, and the impact of the results in the petrophysical answers derived from the measurements. The workflow involves building a layered geological model and modeling the log responses in a model-compare-update loop to obtain the log properties of each layer. While similar methodology has been available in the past, the process was laborious and time consuming, and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…To avoid some of the problems associated with log interpretation in horizontal wells, Rogtec (2017) advocates for tools with azimuthal measurements capacities. Valdisturlo (2013) mentioned that nodules, often intersected on one side of the borehole, could lead to scattering in density-neutron porosity crossplots if the neutron porosity measurement is non-azimuthal and the density measurement is azimuthal. Li et al (2018) showed a method to calculate porosity from sonic logs acquired from horizontal wells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid some of the problems associated with log interpretation in horizontal wells, Rogtec (2017) advocates for tools with azimuthal measurements capacities. Valdisturlo (2013) mentioned that nodules, often intersected on one side of the borehole, could lead to scattering in density-neutron porosity crossplots if the neutron porosity measurement is non-azimuthal and the density measurement is azimuthal. Li et al (2018) showed a method to calculate porosity from sonic logs acquired from horizontal wells.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that saturation calculations using modeled or corrected true resistivities are more accurate compared to measured resistivities in highly deviated wells because measured resistivity has shoulder bed effects in addition to invasion. Valdisturlo et al (2013) mentioned asymmetric invasion profiles and segregation of drilled cuttings as challenges in the interpretation of resistivity logs in horizontal wells. In addition, Ortenzi et al (2012), Wen et al (2013), and Sun et al (2014 have addressed various issues related to the usage and interpretation of resistivity logs in horizontal wells.…”
Section: Introductionmentioning
confidence: 99%